A Firm of One's Own: Experimental Evidence on Credit Constraints and Occupational Choice - Brudevold-Newman, Andrew; Honorati, Maddalena; Ipapa, Gerald; Jakiela, Pamela; Ozier, Owen (The Review of Economics and Statistics, 2024)
We evaluate two interventions targeting young women in Nairobi, Kenya. The first is a multifaceted program involving vocational training, in-kind transfers of physical capital, and ongoing mentoring. The second is an unrestricted cash grant. Both interventions shift women into self-employment, and impacts persist after six years. Both programs also increase income in the short-term, but those effects disappear over time. Though the two treatments have similar impacts on labor market outcomes, women in the multifaceted program report significantly higher wellbeing six years after treatment relative to both women in the control group and those who received the grants.